Influence of Business Intelligence, Environmental Instability, and Eco-Innovation on Financial Outcomes with Cultural Moderation in Digital Age - Endro Andayani; I Gusti Ayu Diah Dhyanasaridewi; Ade Suryana (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This paper aimed to determine whether Business Intelligence (BI), Environmental Uncertainty (EU), and Green Product Innovation (GPI) affect Financial Performance with Organizational Culture as a moderating variable. A total of 311 respondents with minimum managerial level from manufacturing companies listed and not listed on the Indonesia Stock Exchange participated. Data was obtained through questionnaires, and SEM-PLS analysis was used with Smart PLS statistical tool. Research findings show that Environmental Uncertainty affects Financial Performance, while Business Intelligence and Green Product Innovation do not. The impact of Green Product Innovation on Financial Performance is strengthened by Organizational Culture moderation, however, the effect of Business Intelligence and Environmental Uncertainty on Financial Performance is not strengthened by with Organizational Culture (OC) moderation. Academically, this research enriches literature related To Business Intelligence, Environmental Uncertainty, Green Product Innovation, and Financial Performance in the digital era, and can serve as a reference for future research. Practically, the results of this research help companies face competition with faster and more accurate decision making, improving operational quality and customer service. Additionally, for regulators, this research can serve as a basis for formulating policies that support sustainable business, particularly regarding Green Product Innovation and Environmental Uncertainty management.